PENGARUH SUKU BUNGA RIIL DAN PRODUK DOMESTIK BRUTO (PDB) TERHADAP INVESTASI PENANAMAN MODAL ASING (PMA) BERDASARKAN JANGKA PANJANG DAN JANGKA PENDEK DI INDONESIA TAHUN 2010 (Q1) – 2019 (Q4) - Arfanjie Zulham; Richard Rahmat; Mardiana Mardiana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of real interest rates and Gross Domestic Product (GDP) significantly on foreign investment in the long term and short term in Indonesia Period 2010 (Q1) - 2019 (Q4). The method used in this research is descriptive and quantitative methods. The analytical model used is multiple linear regression analysis with the Error Correction Model (ECM) technique (help with EViews 10 software), where the end result will measure the effect of real interest rates and Gross Domestic Product (GDP) significantly on FDI investment in the long term and long term short. The results of this study indicate that real interest rates and gross domestic product (GDP) have a positive and significant effect on FDI in the long run. In the short term, real interest rates and gross domestic product (GDP) have a significant effect on FDI.Keywords: Real Interest Rates, Gross Domestic Product (GDP), Foreign Investment